Analisis Penerapan Sistem Informasi Manajemen Kepegawaian (Simpeg) Dalam Pengelolaan Administrasi Kepegawaian (Studi Kasus Pada Kantor LAPAS Perempuan Kelas III Mamuju) - Rizal Harmawan Samauna (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The management information system assists in carrying out the duties of all State Civil Apparatuses within the Ministry of Law and Human Rights. This system can display the profile of each ASN with the classification of education, training, position and period of service that can be used as a material for consideration by the leadership in the appointment of education and career training as a process in the context of promotion. The purpose of this study was to analyze the implementation of SIMPEG in the management of personnel administration and to analyze the efforts made in optimizing the implementation of SIMPEG in the management of personnel administration. In this study, the authors used descriptive research with qualitative data types. The results of this study are the implementation of SIMPEG has been carried out according to its function to develop the implementation of electronic-based services in improving the quality of personnel optimally, as well as a medium for decision making by the staffing supervisor. Efforts made in optimizing the implementation of SIMPEG are routinely monitoring the behavior of each individual by their direct superiors, then integrated socialization as a form of support from internal and external by maximizing the potential of existing resources, which is only managed by one operator while employees achieve fifty-one people with various needs for personnel data as an effort to realize the management of personnel management based on information technology.